2021
DOI: 10.1146/annurev-psych-070920-023638
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural Foundation of Human Memory

Abstract: Human memory, as a product of the mind and brain, is inherently private and personal. Yet, arising from the interaction between the organism and its ecology in the course of phylogeny and ontogeny, human memory is also profoundly collective and cultural. In this review, I discuss the cultural foundation of human memory. I start by briefly reflecting on the conception of memory against a historical and cultural background. I then detail a model of a culturally saturated mnemonic system in which cultural element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 143 publications
4
78
0
1
Order By: Relevance
“…research on cognitive biases in particular [24][25][26], examining the effects of age, gender, ethnicity and education on the recognition of bias in self versus others. These findings provide original theoretical insights into the persistence of and remedy for the metacognitive biased thinking and have critical real-life implications.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…research on cognitive biases in particular [24][25][26], examining the effects of age, gender, ethnicity and education on the recognition of bias in self versus others. These findings provide original theoretical insights into the persistence of and remedy for the metacognitive biased thinking and have critical real-life implications.…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, we recruited large and diverse samples and examined the influence of demographic factors, including age, gender, ethnicity, and education, on the recognition of myside bias and social biases and the associated self-other asymmetry in everyday contexts. In spite of their importance, demographical factors have not been considered in previous studies in this area and have been much neglected in psychological research [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Figure 1, these processes are deeply embedded in the macro context of the culture that comprises complex systems of meanings and practices (Rogoff et al., 2018; Shweder et al., 1998). Cultural elements, such as beliefs, cognitive styles, tools, and ecology, may operate on memory development by affecting information processing in children and shaping reminiscing activities between parents and children (Wang, 2018, 2021). Indeed, research has revealed cultural differences in children’s independent recall of their experiences as well as their shared memories with parents (for a review, see Wang, 2013).…”
Section: Independent and Shared Memories In The Cultural Contextmentioning
confidence: 99%
“…The development of autobiographical memory, perhaps like any cognitive skills, is the result of interaction between individual characteristics and cultural expectations. Many cultural elements may play a role in shaping the pathways to memory development (Wang, 2021). Research has examined several pathways, including self‐goals, language, emotion knowledge, and perceptual style, as illustrated in Figure 1.…”
Section: Culture Shapes Pathways To Rememberingmentioning
confidence: 99%
See 1 more Smart Citation